2005
DOI: 10.1080/016768390504254
|View full text |Cite
|
Sign up to set email alerts
|

Repair of Medial Orbital Wall Fracture: Transcaruncular Approach

Abstract: The aim of this paper is to demonstrate the safety and the use of the transcaruncular approach as a surgical technique for managing a medial wall fracture. This approach was used in 40 patients with a isolated medial or a combined medial and inferior orbital wall fracture between September 1998 and September 2002. A computed tomographic scan was taken before and after surgery. The ocular motility and enophthalmos were checked before and after surgery. The transcaruncular approach provided the appropriate surgi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…The Lynch incision provides excellent exposure, but it can result in severe scarring or webbing of the medial canthal skin. More recently, the transcaruncular approach has become a major approach to the medial orbit, as it avoids leaving a visible scar 17,18. As with floor fractures, most repairs involve returning the prolapsed soft tissue into the orbit, reconstructing the broken fragments, and then possibly reinforcing the medial wall with similar numerous implant materials, as mentioned previously.…”
Section: Managementmentioning
confidence: 99%
“…The Lynch incision provides excellent exposure, but it can result in severe scarring or webbing of the medial canthal skin. More recently, the transcaruncular approach has become a major approach to the medial orbit, as it avoids leaving a visible scar 17,18. As with floor fractures, most repairs involve returning the prolapsed soft tissue into the orbit, reconstructing the broken fragments, and then possibly reinforcing the medial wall with similar numerous implant materials, as mentioned previously.…”
Section: Managementmentioning
confidence: 99%
“…1,2,7 Medial canthal incision and transcaruncular incision require the use of alloplastic implant materials. 1,2,8 Antral approach has a limited approach to the medial orbital wall. 12 Transnasal endoscopic approach requires the use of expensive equipment, additional education for the surgeon to become fully skilled to manipulate the equipment, and a longer treatment period for the patient and may cause intranasal polyposis.…”
Section: Discussionmentioning
confidence: 99%
“…This approach allows direct access to the medial orbital wall and orbital apex without cutaneous incision or disruption of the medial canthus and insertion of reconstructive materials is possible under direct vision. Recent studies have also shown highly successful and safe results by using this approach for medial orbital fracture repair [7][8][9][10][11]13]. A variation of this technique is demonstrated in a recent cadaver study which uses an approach medial to the caruncle, providing a more direct and avascular path to mid orbit [18].…”
Section: Discussionmentioning
confidence: 99%